2021
DOI: 10.3390/ijerph18052778
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Childhood Left-Behind Experience on the Mental Health of Late Adolescents: Evidence from Chinese College Freshmen

Abstract: A paucity of public service afforded to migrant workers often begets a wide range of social problems. In China, hundreds of millions of migrant worker parents have to leave children behind in their hometowns. This paper investigated the long-term effects of the childhood experience of being left behind on the mental well-being of late adolescents. Mandatory university personality inventory (UPI) surveys (involving psychosomatic problems such as anxiety, depression, and stress) were conducted at a university in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
(31 reference statements)
1
15
1
Order By: Relevance
“…The greater LBE-QOL association among urban freshmen than among rural freshmen observed in this study is similar to the greater negative effect of childhood LBE on mental health among urban freshmen than among rural college freshmen observed in a prior study (13). Because the interactive effect of LBE and place of origin was independent of sociodemographic variables, physical health, depressive symptoms, and academic stress, we speculated that some place-specific contextual factors may magnify or mitigate the detrimental effect of childhood LBE on QOL among University freshmen.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The greater LBE-QOL association among urban freshmen than among rural freshmen observed in this study is similar to the greater negative effect of childhood LBE on mental health among urban freshmen than among rural college freshmen observed in a prior study (13). Because the interactive effect of LBE and place of origin was independent of sociodemographic variables, physical health, depressive symptoms, and academic stress, we speculated that some place-specific contextual factors may magnify or mitigate the detrimental effect of childhood LBE on QOL among University freshmen.…”
Section: Discussionsupporting
confidence: 87%
“…In the main effect model, the significant LBE-QOL association suggests that LBE was independently associated with poor QOL among University freshmen. In previous University students-based studies, childhood LBE was reported to be significantly associated with mental health problems (11)(12)(13)(14)(15), but in the present study, we revealed the independent LBE-QOL association among University freshman students, extending the long-term health outcomes of childhood LBE from mental health problems to worsened QOL. Parents' company and supervision play a vital role in the development and functioning of their children and in preparing them to manage the challenges they will confront in their academic, social, occupational, and cultural lives as adults (42).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Further evidence from China, has shown disadvantage for children who stay behind in outcomes such as anxiety, loneliness, and depression, especially when both parents migrate (Gao et al, 2007;Liu, Li and Ge, 2009;Hu, Lu and Huang 2014;Su et al, 2013;Xu et al, 2017). A recent study conducted with Chinese college freshmen, who were left behind by migrant parents in their childhood, found their psychological health negatively impacted in comparison to their peers (Wu et al, 2021). This study brings into sharp focus the vulnerability of children when their parent/s migrate/s while they are still young and the long-lasting impact it can have on the individual's psychological well-being.…”
Section: Parental Migration and Psychological Health Of Childrenmentioning
confidence: 73%